BIOGEOCHEMISTRY OF BIOMICROELEMENTS IN IRRIGATED SOILS AND CHERRY (Scientific journal of the Fergana State University, 2026)
The article analyzes the microelement composition of irrigated light gray soils (calcisols) and meadow saz soils formed in the Fergana region and the cherry organs grown on them. The processes of migration and accumulation of biomicroelements in these soils and the cherry organs grown on them are also determined, biological absorption coefficients and geochemical spectra are developed.